SNAI1 promotes the development of HCC through the enhancement of proliferation and inhibition of apoptosis. Issue 4 (10th March 2016) - Qi, Jianni; Li, Tao; Bian, Hongjun; Li, Feifei; Ju, Ying; Gao, Shanshan; Su, Jingran; Ren, Wanhua; Qin, Chengyong
Abstract : SNAI1, a zinc‐finger transcription factor, plays an important role in the induction of epithelial–mesenchymal transition (EMT) in various cancers. However, the possible functions of SNAI1 in the proliferation and apoptosis of hepatocellular carcinoma have not been clearly identified. In this study, we investigated the effects and mechanisms of SNAI1 in the proliferation and apoptosis of hepatocellular carcinoma using clinical samples and cell lines. We found that SNAI1 is highly expressed in the tissues of liver cancer compared with adjacent nontumor tissues. SNAI1 is also highly expressed in the hepatoma cell lines HepG2, SMMC‐7721, and BEL‐7402 compared with the human normal liver cell line L02. We also observed that SNAI1 expression was correlated with distal metastasis, incomplete tumor capsule formation, and histological differentiation in hepatocellular carcinoma (HCC). Moreover, we demonstrated that knockdown of SNAI1 via lentiviral vectors of RNAi against SNAI inhibited cell proliferation by inducing G1 arrest, which was accompanied by the downregulation of cyclin D1 but not that of cyclin A. In addition, knockdown of SNAI1 promoted apoptosis by decreasing the expression of Bcl‐2. In conclusion, our findings revealed that SNAI1 is involved in the development of hepatocellular carcinoma via regulating the growth and apoptosis of tumor cells. Abstract : The zinc‐finger transcription factor SNAI1 was highly expressed in liver cancer tissues and hepatoma cell lines. Further, SNAI1 inhibited apoptosis by increasing the expression of Bcl‐2 and promoted growth by upregulating Cyclin D1 in HepG2 cells. These results imply that SNAI1 is involved in hepatocarcinogenesis via regulating growth and apoptosis, not just by its effect on the epithelial–mesenchymal transition.